KORELASI KETERAMPILAN MEMBACA APRESIATIF DENGAN KETERAMPILAN MENULIS TEKS CERPEN SISWA KELAS XI SMA ADABIAH 2 PADANG - Apriyenti, Lisa; Tressyalina, Tressyalina (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
ABSTRACTÂ The purpose of this research was to describe things as follows. First, describes the skills of reading appreciative grade XI Senior High School 2 Padang. Second, it describes the writing skills text cerpen grade XI Senior High School 2 Padang. Third, explain the relationship between the reading appreciative with writing skill text cerpen grade XI Senior High School 2 Padang. This type of research correlation between appreciative reading skills and writing skills text cerpen of grade XI Senior High School 2 Padang is quantitative research with descriptive methods. Based on the reslt of the study, the following three things concluded. First, the appreciative reading skills of grade XI Senior High School 2 Padang are in good qualification (81,32). Second, the writing skills text cerpen on grade XI Senior High school 2 Padang are in good qalification (82.24). Third, there is a significant correlation between appreciative reading skills and writing skills text cerpen of grade XI Senior High School 2 Padang at n-1 degress freedom and a sicnificant level of 95%.Â Kata Kunci: korelasi, membaca apresiatif, menulis teks cerpen